2006
DOI: 10.1111/j.1751-3928.2006.tb00293.x
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry and Origin of Ananai Stratiform Manganese Deposit in the Northern Chichibu Belt, Central Shikoku, Japan

Abstract: . Major and trace element contents are reported for Permian manganese ore and associated greenstone from the Ananai manganese deposit in the Northern Chichibu Belt, central Shikoku, Japan. The manganese deposit occurs between greenstone and red chert, or among red chert beds. Chemical compositions of manganese ore are characterized by enrichments in Mn, Ca, P, Co, Ni, Zn, Sr and Ba, and negative Ce and positive Eu anomalies relative to post‐Archean average Australian Shale (PAAS). Geochemical features of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 33 publications
(27 reference statements)
1
24
0
1
Order By: Relevance
“…1b). The massive basaltic lava contains Ti-rich augite, Ti-rich biotite, K-rich kaerusutite and apatite as relict igneous minerals in addition to pseudomorphs after olivine, feldspar and titanomagnetite, in agreement with the alkaline affinity of metaigneous rocks in the Kamiyoshida unit (Fujinaga et al, 2006).…”
Section: Geologysupporting
confidence: 49%
See 1 more Smart Citation
“…1b). The massive basaltic lava contains Ti-rich augite, Ti-rich biotite, K-rich kaerusutite and apatite as relict igneous minerals in addition to pseudomorphs after olivine, feldspar and titanomagnetite, in agreement with the alkaline affinity of metaigneous rocks in the Kamiyoshida unit (Fujinaga et al, 2006).…”
Section: Geologysupporting
confidence: 49%
“…In contrast, Murata et al (2009) suggested that the region of high-P/T metamorphism extends further south from the Sasagatani fault based on the widespread occurrence of sodic amphibole (magnesioriebeckite to riebeckite) in metabasite. Metabasites in the Mikabu and Kashiwagi units are mostly derived from tholeiitic oceanic-floor basalts, whereas those in the Kamiyoshida unit include within-plate alkaline basalt (Suzuki and Ishizuka, 1998;Fujinaga et al, 2006). Formation of single phase magnesioriebeckite/riebeckite in alkaline basalt does not require high-P/T conditions, and thus it remains unclear whether or not the Kamiyoshida unit in the study area underwent the Sanbagawa metamorphism.…”
Section: Geologymentioning
confidence: 99%
“…The other is the stratiform Mn deposit that is mainly distributed in the Jurassic accretionary complex (Mino-Tanba, Chichibu and Northern Kitakami Belts) and is interbedded with chert or associated with greenstone. The Mn deposit is considered to have been formed by inflow of oxic deepwater into a stagnant anoxic ocean floor Komuro and Wakita, 2005) or by hydrothermal activity related to hotspot volcanism (Fujinaga et al, 2006). In addition to these Fe-Mn and Mn oxide deposits, volcanogenic massive sulfide (VMS) deposits, termed as Besshi-type deposits, occur in the Sanbagawa highpressure metamorphic belt, southwest Japan.…”
Section: Introductionmentioning
confidence: 99%
“…This result is supported by lithological, chemical and isotopic evidence. Fujinaga et al (2006) suggested that the deposit associated with basic volcanic rock of the Ananai deposit in the Chichibu Terrane formed hydrothermally due to hot-spot volcanism. Thick carbonate layers and specific stratigraphic succession similar to those of the stratiform manganese deposits in the accretionary complexes are not recognized in the ODP cores, suggesting that carbonate layers did not form in the Cenozoic oxic pelagic environment.…”
Section: Implications For Manganese Mineralization In Accretionary Comentioning
confidence: 99%